Ethical Behaviors Affecting Kalyanamitra Dhamma’s Principles of Educational Institution Administrators under Surin Primary Educational Service Area Office 1 - Yuenyong, Sirasit; Saeng-ngern, Supot; Panyatharo, Thongpean (Rajapark Journal, 2025)
This research aimed to study 1) ethical behaviours of educational institution administrators, 2) the application of Kalyanamitra Dhamma’s principles of educational institution administrators, 3) the relationship between ethical behaviours affecting the Principles of Kalyanamitra Dhamma, and 4) ethical behaviours affecting Kalyanamitra Dhamma’s Principles of Educational Institution Administrators under Surin Primary Educational Service Area Office 1. The sample consisted of 169 school administrators, selected through a proportional stratified random sampling method. The research instrument was a 5-point rating scale questionnaire with a reliability coefficient of 0.97. Data were analyzed using percentages, means, standard deviations, Pearson’s correlation coefficient, and stepwise multiple regression analysis. The research results found that: 1) the overall ethical behaviours of educational institution administrators were at a high level, 2) the overall having of the principles of Kalyanamitra Dharma was at the highest level, 3) there was a high positive correlation between ethical behaviours affecting the principles of Kalyanamitra Dhamma (rXY = 0.65) with statistical significance at the .01 level, and 4) two aspects of ethical behaviours, work management and personnel management, affected the principles of Kalyanamitra Dhamma, jointly explaining 43.40% of the variance with statistical significance at the .05 level, with a standard error of estimate of ±0.23.